Meningkatkan Keterampilan Kerjasama Siswa Pada Tema Pengalamanku Menggunakan Model Pembelajaran Number Head Together (NHT) - Tyaswati NA (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to improve collaboration skills in thematic learning in grade 1 students of SD Negeri Panjang 03 Semarang Regency using the Number Head Together (NHT) learning model. This type of research is used classroom action research (CAR) which consists of two cycles. Each cycle consists of stages of action planning, action implementation, observation, and reflection. The data collection instruments used the assessment rubric for the implementation of student activities, questionnaires, and group worksheets. Data analysis was performed using comparative analysis which compares the initial conditions before the action with the results of cycle I and cycle II. The results showed that the Number Head Together (NHT) learning model could improve collaboration skills as seen from the increase in the total score of students in each cycle. The percentage increase in student scores from pre-cycle by 25% (6 students), cycle I 46% (11 students), and cycle II 92% (22 students). The data shows an increase in the percentage of students achieving a minimum score in collaboration skills. Keywords: Number Head Together, collaboration skills